The Relationship Of The Influence Of Smartphone Users On Sex Behavior In Adolescent Boys And Women In Hamlet Vii Sei Rattan Village, Percut Sei Tuan District, Deli Serdang - Dessy Ratna (Science Midwifery, 2022)
Adolescent sexual behavior is behavior involving physical touching of limbs between men and women who have reached the stage of intimate relationships, usually carried out by married couples, the results of a survey on the incidence of sexual intercourse from 3 million teenagers who stated that they had had premarital sexual behavior in 2007 became 3.7 million adolescents in 2012, the purpose of this study was to determine the relationship of smartphone users to sexual behavior in adolescent boys and girls, the type of research conducted was descriptive analytic and (cross sectional) this study aimed to see the phenomenon of the description of adolescent sexual behavior This research was conducted from January to August with an internal population of 140 adolescents while the sample in this study the authors took as many as 58 adolescents, in the implementation of the study the authors collected data through secondary and primary data by conducting interviews and research instruments. in the form of a questionnaire, managing data by editing, coding, tabulating, data entry. This study uses SPSS with the chi-square test. It can be seen from 58 that the majority of respondents who have risky sexual behavior are 36 (62.1%) and the minority who have risky sex behavior is 22 ( 37.9%), and 58 the majority who have a negative influence on smartphone users are 36 (62.1%) and the minority who have a positive influence on smartphone users are 22 (37.9%), the statistical test results obtained the Odd Ratio (OR) = 6.125 CI = 1,899 19,760 and P value 0,004 < 0, Suggest to young men and women to use smartphones more in a positive direction such as to access lessons, sing, play and to watch positive things and avoid negative things in the smartphone so that it can prevent behavior risky sexual behavior among young men and women.